Religious Freedom, Multiculturalism, Islam : Cross-reading Finland and Ireland - Sakaranaho, Tuula (Brill Book Archive Part 1, ISBN: 9789004472495., 2006)
This is a comparative study of Muslims in Finland and the Republic of Ireland, from the perspective of religious freedom and multiculturalism. The book consists of three parts: the first part discusses religious freedom and multiculturalism from a conceptual point of view and mainly within the context of Western Europe, culminating in the cases of Finland and Ireland; the second part deals with the establishment of Muslim communities in Europe in general, and in Finland and Ireland in particular; and the third part concerns Islam and education in these respective countries.